2006
DOI: 10.1111/j.1574-6941.1997.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Iprodione degradation by isolated soil microorganisms

Abstract: Three bacterial strains were isolated from soils adapted to iprodione and identified as Pseudomonas fluorescens, Pseudomonas sp. and Pseudomonas paucimobilis. The first two strains transformed iprodione to N‐(3,5‐dichlorophenyl)‐2,4‐dioxoimidazolidine (II) and under restrictive conditions to 3,5‐dichlorophenylurea acetic acid (III); the latter subsequently degraded II to III and III to 3,5‐dichloroaniline (3,5‐D). We constructed bacterial combinations consisting of Pseudomonas paucimobilis plus one of the ipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…However, previous studies indicate that this is unlikely to be a common occurrence (Cohen et al 1999). Instead, it is more likely that the chemicals are degraded by microbial action (Mercadier, Vega & Bastide 1997;Armbrust 2001) and the most probable site where this occurs is the thatch layer in a golf green (Sigler et al 2000). This layer of undecomposed plant material occurs at the soil surface and in some cases can be several centimetres deep.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies indicate that this is unlikely to be a common occurrence (Cohen et al 1999). Instead, it is more likely that the chemicals are degraded by microbial action (Mercadier, Vega & Bastide 1997;Armbrust 2001) and the most probable site where this occurs is the thatch layer in a golf green (Sigler et al 2000). This layer of undecomposed plant material occurs at the soil surface and in some cases can be several centimetres deep.…”
Section: Discussionmentioning
confidence: 98%
“…These authors reported that B. thiooxidans and S. Paucimobilis degraded lindane after 3 days of aerobic incubation. Mercadier et al (1997) reported that 50% of fungicide iprodione was degraded by bacterial isolated from soil as Pseudomonas sp. Atrazine, monocrotophos, alachlor and 4-chlorophenol have been degraded also by soil microorganism (Westerberg et al, 2000;Bhadbhade et al, 2002;Strong et al, 2002).…”
Section: Degradation Of Pesticides By Soil Microorganismsmentioning
confidence: 99%
“…The decline in iprodione residues coincided with prolonged soil and air temperatures greater than 0°C, suggesting that any such additional factors may be influenced by temperature. It is well established that both iprodione (Walker, 1987;Mercadier et al, 1997;Zadra et al, 2006) and chlorothalonil (Motonaga et al, 1998;Singh et al, 2002) are rapidly degraded by microorganisms in the soil. Less research has been conducted on phyllosphere impacts on fungicide persistence and the results of those studies have often been conflicting (Lukens & Ou, 1976;Frederick et al, 1996;Sigler et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…have been identified as organisms that readily metabolize iprodione to its primary metabolite, 3,5-dichloroaniline (Mercadier et al, 1997;Zadra et al, 2006). A number of studies suggest that repeated applications of iprodione may lead to increased degradation rates in the soil, presumably due to the build-up of organisms that rapidly metabolize the parent compound (Walker, 1987;Mercadier et al, 1997;Garcia-Cazorla & Xirau-Vayreda, 1998). Sigler et al (2003), however, did not observe enhanced biodegradation of iprodione on turfgrass foliage over a period of eight applications, instead concluding that sorption and plant uptake drove depletion rates.…”
Section: Introductionmentioning
confidence: 99%